Relationship between Postural Deformities and Frontal Function in Parkinson’s Disease - Satoko Ninomiya; Akihiko Morita; Hiroko Teramoto; Takayoshi Akimoto; Hiroshi Shiota; Satoshi Kamei (Parkinson's Disease)
Postural deformities and executive dysfunction (ED) are common symptoms of Parkinson’s disease (PD); however, the relationship between postural deformities and ED in patients with PD remains unclear. This study assessed the relationship between postural deformities and ED in patients with PD. Sixty-five patients with sporadic PD were assessed for the severity of postural deformities and executive function. The severity of postural deformities was scored using the United Parkinson’s Disease Rating Scale item 28 score: no postural deformity (0), mild postural deformities (1), or severe postural deformities (2–4). Executive function was assessed using the Behavioral Assessment of the Dysexecutive Syndrome (BADS) and an age-controlled standardized BADS score <70 was defined as ED. Age-controlled standardized BADS scores were compared across the three groups using the Kruskal-Wallis test. Relationship between ED and the severity of postural deformities was assessed using the Mann-Whitney U test. Age-controlled standardized BADS score significantly differed among the three groups P=0.005. ED was significantly related to the severity of postural deformities P=0.0005. The severity of postural deformities was associated with a lower age-controlled standardized BADS score and ED, and these findings suggest that postural deformities were associated with frontal dysfunction in patients with PD.